Thiamine deficiency in pregnancy and lactation: implications and present perspectives - Kareem, Ozaifa; Nisar, Sobia; Tanvir, Masood; Muzaffer, Umar; Bader, G. N. (Frontiers in Nutrition, 2023)
During pregnancy, many physiologic changes occur in order to accommodate fetal growth. These changes require an increase in many of the nutritional needs in order to prevent long term consequences on both the mother and the offspring. One of the main vitamins that are needed throughout the pregnancy is Thiamine (vitamin B1) which is a water-soluble vitamin that plays an important role in many metabolic and physiologic processes in the human body. Thiamine deficiency during pregnancy can cause can have many cardiac, neurologic, and psychologic effects on the mother. It can also dispose the fetus to gastrointestinal, pulmonological, cardiac, and neurologic conditions as well as autism disorders. This paper reviews the recent published literature about thiamine and its physiologic roles, thiamine deficiency in pregnancy, its prevalence, and its consequences, and highlights the knowledge gaps within these topics.